Effects of internal migration on labour market behaviour of families left-behind in Vietnam - David Granada Donato (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2022)
This document explores the implications of a migratory shock (in the form of household member(s) leaving) on the labour market behaviour of individuals left-behind in Vietnam. In addition, various coping mechanisms exhibited by each age group and their implications regarding sectoral labour allocation are further explored. Using panel data of 2,200 households in six waves and a DiD specification, the results suggest an increase in the likelihood of working for the elderly in agriculture that is most likely associated with higher labour invested in livestock activities. The results are robust to different specifications. Moreover, this coping mechanism of increased work is exhibited by those families that do not receive remittances and seems to last (even increase) for up to three periods after the migratory shock occurs. Interestingly, there is also evidence of diminishing returns on working probability when the share of migrants in the household increase.
Keywords: J61; O15; P25; R23; 330; Migration; Left-Behind; Labour Market; Agriculture